Strategies for the stimulation of critical thinking in students with intellectual disabilities - Chávez, Lina (2021)
Education is the central column of the people, so it must be available to anyone. Creativity can be developed through its usefulness benefits everyone, especially students with intellectual disabilities, because it is an effective tool for acceptable inclusion in society. The objective of this work was to know basic concepts of critical thinking and the variables that are used with this population to develop them. Therefore, a descriptive and analytical study has been carried out with a documented review of various articles published from reliable sources, databases, and repositories. From the results obtained, various creative strategies applied to students with intellectual disabilities were known, which allows them to develop multiple skills and transfer them to solving everyday problems. Therefore, it is concluded that all people, including students with intellectual deficits, can develop creative thinking with various strategies for its stimulation.